Model of Education in Renewable Energies from the Public Engagement and the Energetic Attitude - Ballesteros-Ballesteros, Vladimir Alfonso; Gallego-Torres, Adriana Patricia (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The current energy crisis of the planet is a reality to which we cannot turn a blind eye. Now more than at other times, the energy problems are sharpened, resulting in the production, transformation, distribution and consumption of energy that led to the evident depletion of fossil fuels, environmental problems generated by the exploitation, transportation and use of natural resources. natural resources, climate change, pollution, among others. The work presented here, has the main intention of proposing a conceptual model based on a theoretical construction from a mixed methodology of documentary analysis, from the formulation of three categories: education in renewable energies (EER), public commitment ( CP) and the conceptualization developed by our team on energy attitude (AE); all this added to the necessary interactions that are generated from participatory democracy and community social construction that aims to involve society as the main structure and not as an end. Secondly, the importance of contributing to the development of the research field of Education in Renewable Energy, due to the discussions that currently arise in the face of the lack of social responsibility in energy and the disinterest in the use of alternative energies as a strategy of reduction of the environmental problems of the context; finally, the need to formulate new ways for the implementation of the use of renewable energies by citizens with the intention of mitigating the problems derived from an excessive development of science and technology that has been problematic in recent decades.